2016
DOI: 10.1093/mnras/stw1583
|View full text |Cite
|
Sign up to set email alerts
|

Accretion of pristine gas and dilution during the formation of multiple-population globular clusters

Abstract: We study the interaction of the early spherical GC wind powered by Type II supernovae (SNe II) with the surrounding ambient medium consisting of the gaseous disk of a star forming galaxy at redshift z > ∼ 2. The bubble formed by the wind eventually breaks out of the disk, and most of the wind moves directly out of the galaxy and is definitively lost. The fraction of the wind moving nearly parallel to the galactic plane carves a hole in the disk which will contract after the end of the SN activity. During the i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 60 publications
2
50
0
Order By: Relevance
“…One of the main findings emerging from the study by D' Ercole et al (2016) is that for a given density distribution the return of the pristine gas takes longer for more massive clusters. This result, in conjunction with the high sensitivity of the degree of the hot bottom burning nucleosynthesis experienced by massive AGBs to the metallicity, provide an explanation of the correlation between the shape of the Mg-Al distribution and the mass and metallicity of the clusters found in recent studies (Carretta et al 2009a,b,c;Pancino et al 2017). D'Ercole et al (2016 clearly demonstrated that the mass of the cluster has a strong effect on the extent of the chemical pollution patterns of the species touched by proton-capture nucleosynthesis.…”
Section: Possible Interpretation Of Observed Propertiessupporting
confidence: 62%
“…One of the main findings emerging from the study by D' Ercole et al (2016) is that for a given density distribution the return of the pristine gas takes longer for more massive clusters. This result, in conjunction with the high sensitivity of the degree of the hot bottom burning nucleosynthesis experienced by massive AGBs to the metallicity, provide an explanation of the correlation between the shape of the Mg-Al distribution and the mass and metallicity of the clusters found in recent studies (Carretta et al 2009a,b,c;Pancino et al 2017). D'Ercole et al (2016 clearly demonstrated that the mass of the cluster has a strong effect on the extent of the chemical pollution patterns of the species touched by proton-capture nucleosynthesis.…”
Section: Possible Interpretation Of Observed Propertiessupporting
confidence: 62%
“…Strong radiative cooling and the stalling of stellar winds promote rapid star formation, significant gas retention, and inhibit the mixing of polluted and pristine gas, which produces a centrally concentrated population of E composition stars. Following the model presented by D'Ercole et al (2016), core-collapse SNe halt star formation for ∼15−40 Myr until enough pristine gas can be accumulated to start the second, delayed formation phase. After ∼40 Myr, the D' Antona et al (2016) model indicates that < 8 M ⊙ AGB stars can start contributing processed gas and mixing with pristine material.…”
Section: Ngc 6402 Chemical Composition Implications For Cluster Formamentioning
confidence: 94%
“…Despite the current GC formation scenarios are still uncertain (e.g., Renzini et al 2015), we report in Table 1 the possible ranges of a few relevant quantities expected during the formation of the first generation stars in GCs of two different masses and within the AGB scenario (D'Ercole et al 2008(D'Ercole et al , 2016. D'Ercole et al (2008) study the formation of one proto-GC of stellar mass 10 6 M and half-mass radius of 16 pc and another more massive one, characterised by a stellar mass 10 7 M and an half mass radius of 35 pc.…”
Section: Can We Observe Active Gcs?mentioning
confidence: 99%